The Mapping of the Strategic Issues that Affect the Local Governments’ Performance - Bastari, Iman; Maarif, M. Syamsul; Puspitawati, Herien; Baga, Lukman M. (UI Scholars Hub, 2015)
arious strategic issues that have an effect towards the performance of local governments in Indonesia are very complex just like the local governments in other countries, as investigated on previous researches. These strategic issues, which include the fiscal capacity, the background of the local leaders as entrepreneurs, and the capacity of management, would have significant influence towards the performance of local governments. This research tries to conduct the investigation towards other strategic issues i.e. the characteristics of local governments, the public entrepreneurship, the strategic environment, and the enforcement of ethics and accountability of bureaucracy, which is both very important and very certain in terms of the influence towards the performance of local governments. As the initial phase of thorough research is related to the influence of public entrepreneurship towards the performance of local government, the mapping needs to be conducted in order to ensure the level of importance and certainty of the strategic issues with the use of the Strategic Assumption Surfacing Test (SAST) approach involving the selected experts through limited Focus Group Discussion (FGD). The results of data processing would give an overview that the characteristics of local governments and its elements (the regional assets, the fiscal capacity, the capacity of management and entrepreneurial behavior), the public entrepreneurship (innovation, the creativity of the individuals within bureaucracy, proactiveness, risk-taking and public-oriented) are the strategic issues, which are important and certainly influence the performance of local governments in Indonesia.